Electrochemical Biosensing in Cancer Diagnostics and Follow‐up. Issue 8 (30th April 2018) - Freitas, Maria; Nouws, Henri P. A.; Delerue‐Matos, Cristina
Abstract: In cancer, screening and early detection are critical for the success of the patient's treatment and to increase the survival rate. The development of analytical tools for non‐invasive detection, through the analysis of cancer biomarkers, is imperative for disease diagnosis, treatment and follow‐up. Tumour biomarkers refer to substances or processes that, in clinical settings, are indicative of the presence of cancer in the body. These biomarkers can be detected using biosensors, that, because of their fast, accurate and point of care applicability, are prominent alternatives to the traditional methods. Moreover, the constant innovations in the biosensing field improve the determination of normal and/or elevated levels of tumour biomarkers in patients' biological fluids (such as serum, plasma, whole blood, urine, etc.). Although several biomarkers (DNA, RNA, proteins, cells) are known, the detection of proteins and circulating tumour cells (CTCs) are the most commonly reported due to their approval as tumour biomarkers by the specialized entities and commonly accepted for diagnosis by medical and clinical teams. Therefore, electrochemical immunosensors and cytosensors are vastly described in this review, because of their fast, simple and accurate detection, the low sample volumes required, and the excellent limits of detection obtained. The biosensing strategies reported for the six most commonly diagnosed cancers (lung, breast, colorectal, prostate, liver and stomach) are summarized and the distinct phases of the sensors' constructions (surface modification, antibody immobilization, immunochemical interactions, detection approach) and applications are discussed. Abstract :